In Hospital Outcome of Acute Anterior Myocardial Infarction in Diabetic and Non-Diabetic Patients - Md. Suhail Alam; Md. Shahabuddin; Md. Abdul Mukid; Farzana Tazin; Tafhema Tarin; Partha Sarathi Roy Chowdhury (International Journal of Medical Research and Review, 2023)
Background: Patients with acute anterior myocardial infarction and diabetes have a poor prognosis. Objectives: To see the in-hospital outcome of acute anterior myocardial infarction in diabetic and non-diabetic patients. Methodology: This cross-sectional observational study was conducted in the Department of Cardiology, Sylhet MAG Osmani Medical College Hospital, Sylhet over a period of two years from July 2015 to June 2017. A total of 100 acute anterior MI patients (50 diabetic and 50 non diabetic) were included in this study. Acute anterior MI patients admitted after 6 hours of symptom onset or who did not receive streptokinase were excluded. Results: Male predominance was obvious in both groups [40 (80%) versus 42 (84%); p>0.05] in diabetic and non-diabetic group respectively. Mean age was 53.34 ± 11.32 and 54.84 ± 14.12 years in diabetic and non-diabetic groups respectively. Dyslipidemia [6 (12%) versus 6 (12%); p >0.05], Smoking [32 (64%) versus 34 (68%); p >0.05] and Family history of cardiovascular disease [6 (12%) versus 4 (8%); p >0.05] were similar among diabetic and non-diabetic respectively. Hypertension was found more among non-diabetic [27 (54%) versus 19 (38%); p>0.05] but difference was not statistically significant. Diabetic group had more Apical Anterior MI [22 (44%) versus 19 (38%); p<0.05] and Extensive Anterior MI [20 (40%) versus 11 (22%); p<0.05] while non-diabetic group had more Septal MI [10 (20%) versus 3 (6%); p<0.05] and Mid Anterior MI [10 (20%) versus 4 (8%); p<0.05]. LV ejection fraction was found significantly low in diabetic patients [43.96 ± 5.95 versus 53.68 ± 6.36; p<0.01]. Killip Class III was more in diabetic [24 (48%) versus 9 (18%); p<0.01] and Killip Class I was more in non-diabetic group [18 (36%) versus 3 (6%); p<0.01] according to Killip classification of HF which was statistically significant between the two groups. Atrial Fibrillation was more in diabetics [6 (12%) versus 1 (2%); p<0.05] while sinus tachycardia was more among non-diabetics [20 (40%) versus 5 (10%); p<0.05] which are statistically significant. Diabetic group had more acute MR [2 (4%) versus 0 (0%); p>0.05] but was not significant. Death was more in diabetic group than that of non-diabetic group [7 (14%) versus 3 (6%); p>0.05] but it was statistically not significant. Conclusion: It is concluded from the present study that in hospital outcomes of acute anterior myocardial infarction are worse in diabetic patients than in non-diabetic patients.